2015
DOI: 10.1002/art.39250
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Neutrophil Chemorepellent Soluble Dipeptidyl Peptidase IV in Decreasing Inflammation in a Murine Model of Arthritis

Abstract: Objective To determine whether an intraarticular injection of the neutrophil chemorepellent dipeptidyl peptidase IV (DPPIV; CD26) can attenuate inflammation and decrease the severity of arthritis in a murine model. Methods DBA/1 mice were immunized with type II collagen/Freund's complete adjuvant to produce collagen-induced arthritis (CIA). On day 25 postimmunization, recombinant human DPPIV (rhDPPIV) or phosphate buffered saline was injected intraarticularly, and arthritis severity scores were recorded 3 ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…DPPIV release was also significantly higher in CPCs-PL than in ACs-PL. In a murine model of collagen-induced arthritis (CIA), it has been demonstrated that DPPIV injection decreases the overall extent of inflammation and articular damage around the arthritic joint and periarticular tissue [83].…”
Section: Discussionmentioning
confidence: 99%
“…DPPIV release was also significantly higher in CPCs-PL than in ACs-PL. In a murine model of collagen-induced arthritis (CIA), it has been demonstrated that DPPIV injection decreases the overall extent of inflammation and articular damage around the arthritic joint and periarticular tissue [83].…”
Section: Discussionmentioning
confidence: 99%
“…Low levels of DPPIV activity or soluble CD26 were observed in immuno-suppressed conditions including some tumors; whereas high levels occur in other tumors, infectious, inflammatory and liver diseases [2]. These qualitative or quantitative changes may be important in the pathogenesis of RA, since DPPIV as a result of its N-terminal X-Pro cleaving activity regulates chemotactic responses to the inflammatory chemokines CCL3- 5,11 and 22,CXCL2,[9][10][11][12], including SDF-1 [24,25]. In addition, it regulates other biologically active peptides such as NPY and VIP, recently implicated in RA [26].…”
Section: Discussionmentioning
confidence: 99%
“…In synovial tissue and in synovial fluid, significantly lower expression and membrane activity of CD26 were detected on mononuclear cells of synovial fluid [10]. Furthermore, inhibition of synovial DPPIV activity had led to increased cartilage destruction, pointing to DPPIV as a protective factor of articular cartilage [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Being able to repel neutrophils out of the affected tissue might be therapeutic. Treatment with inhaled DPPIV prevented an increase in lung neutrophils in a mouse model of ARDS (Herlihy et al, 2013a), and localized injections of DPPIV decreased symptoms of arthritis in a mouse model (Herlihy et al, 2015). We then found that the DPPIV receptor is the proteaseactivated G protein-coupled receptor PAR 2, that PAR 2 agonists induce human neutrophil chemorepulsion, and when administered by aspiration into the airways, PAR 2 agonists show good efficacy at reducing the inappropriate influx of neutrophils into the lungs in a mouse model of ARDS (White et al, 2018).…”
Section: Development Of Potential Therapeutics Based On Dictyosteliummentioning
confidence: 95%